Patterns of recurrent injuries among US high school athletes, 2005-2008 - Swenson, D. M.; Yard, E. E.; Fields, S. K.; Comstock, R. D. (The American Journal of Sports Medicine, 2009)
Background High school sports participants sustain millions of injuries annually; many are recurrent injuries that can be more severe than new injuries.